2021
DOI: 10.3390/ma14102617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Zeolite Doses on Plants and Soil Physicochemical Properties

Abstract: Thousands of tons of zeolitic materials are used yearly as soil conditioners and components of slow-release fertilizers. A positive influence of application of zeolites on plant growth has been frequently observed. Because zeolites have extremely large cation exchange capacity, surface area, porosity and water holding capacity, a paradigm has aroused that increasing plant growth is caused by a long-lasting improvement of soil physicochemical properties by zeolites. In the first year of our field experiment per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…The Net Assimilation Rate (NAR) of the plant at 15 days after planting positively correlated with the NAR of the plant at 45 days after planting (0.640) and the plant at 75 days after planting (0.749), as well as negatively correlated with the yield (Y) (-0.859). Similarly, the NAR of the plant at 45 days after The increase in production as a result of the addition of Zeolite may result from the release of potassium, calcium, magnesium and some microelements to the root zone by the zeolite exchange complex [11]. Since all plots of land were fertilized with the same amount of nitrogen, there should be no difference in yield; however, the combined effect of zeolite and nitrogen gives important results in this regard, as stated by [12], who observed that the use of zeolites increased the effectiveness of nitrogen application in the soil by about 16-22% due to better nitrogen distribution in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The Net Assimilation Rate (NAR) of the plant at 15 days after planting positively correlated with the NAR of the plant at 45 days after planting (0.640) and the plant at 75 days after planting (0.749), as well as negatively correlated with the yield (Y) (-0.859). Similarly, the NAR of the plant at 45 days after The increase in production as a result of the addition of Zeolite may result from the release of potassium, calcium, magnesium and some microelements to the root zone by the zeolite exchange complex [11]. Since all plots of land were fertilized with the same amount of nitrogen, there should be no difference in yield; however, the combined effect of zeolite and nitrogen gives important results in this regard, as stated by [12], who observed that the use of zeolites increased the effectiveness of nitrogen application in the soil by about 16-22% due to better nitrogen distribution in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Zhuo et al 30 found that soil treated with a combination of biochar and mycorrhiza had a considerable increase in pH. Moreover, various researchers reported that biochar and zeolite increase the soil EC value 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, research on natural super absorbents (NHAs) as environmental friendly and cost-effective alternatives to synthetic SAPs has greatly accelerated. Because of the very low swelling capacity of inorganic natural superabsorbent (Chen et al, 2021;Ibrahim & Alghamdi, 2021;Noh et al, 2015;Omar et al, 2015Omar et al, , 2017 and their adverse effects on the soil fertility and structure (Liu et al, 2017;Szatanic-Kloc et al, 2021), focus has been placed on the NHAs based on large volume biopolymers from either the group of polysaccharides or proteins (Abdulhameed et al, 2020;Llanes et al, 2020;Muhammad et al, 2016;Sarmah & Karak, 2020;Xi & Zhang, 2021;Xiao et al, 2017;Zou et al, 2012). Cellulose, starch, chitosan, various gums and gelatin are the most frequently considered naturally sourced components for NHAs.…”
Section: Introductionmentioning
confidence: 99%